Cross tolerance of carmine spider mite, Tetranychus cinnabarinus, to abamectin and high temperature - FENG Hong-zu; LIU Ying-hong; HE Lin; LI Ming; LU Rui-e (浙江大学学报. 农业与生命科学版)
The susceptible strain (SS), the abamectin resistant strain (RA) and the high temperature tolerant strain (RH) from Tetranychus cinnabarinus were used to study cross tolerance to abamectin and high temperature using the methods of bioassay and fluorescent real time quantitative PCR. The results showed that, under high temperature (46 ℃), median lethal time (LT50) and median lethal concentration (LC50) of abamectin toxicity to T. cinnabarinus were in the order of RH > RA > SS and RA > RH > SS, respectively, which of the strains RH, RA were significantly higher than SS, indicating that the long-term heat stress could induce abamectin-resistance and heat-resistance. The contents of free radicals (<inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/j.issn.1008-9209.2010.02.007-I004.jpg"/>) of SS, RA, and RH treated with abamectin were 2.08, 1.85, and 2.00-fold higher than those of their untreated controls, respectively, and the superoxide dismutase (SOD) activities were 3.81, 4.84, and 4.26-fold higher, and the activities of catalase (CAT) and peroxidase (POD) were higher than those of their untreated controls. The free radical contents and the activities of SOD, CAT and POD in T. cinnabarinus exhibited the same tendency at high temperature (40 ℃) and low temperature (4 ℃). The result above showed that the <inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/j.issn.1008-9209.2010.02.007-I005.jpg"/>, the activities of SOD, CAT and POD in T. cinnabarinus were related to abamectin and hot (cold) stimulates, and the induced abilities of RA and RH to protect the enzyme activity were strengthened under long-term abamectin or high temperature stress. Under the normal condition, the mRNA level of TcHSP90 was 1.64 and 1.29-fold higher in the RA and RH than that in SS, respectively. After treatment of abamectin, high temperature (40 ℃) and low temperature (4 ℃), the TcHSP90 mRNA levels of RA and RH were also significantly higher than SS, indicating that HSP90 played an important role in the drug-resistance and heat-resistance.